Prevalence of polypharmacy in patients with a diagnosis of liver cirrhosis treated in the Gastroenterology service of the La Raza National Medical Center - Martín Rivera-Huizar; Javier I. Carrillo-Rojas; Francisca Martinez-Silva (Annals of Hepatology)
Introduction and Objectives: The need for multiple drugs to treat the complications associated with liver cirrhosis, as well as its comorbidities, places patients with chronic liver disease at high risk of polypharmacy with the possible use of unnecessary drugs and drug interactions. We propose to evaluate the prevalence of polypharmacy in patients with liver cirrhosis in our unit. Materials and Patients: In a descriptive, observational, retrospective study with the aim of evaluating men and women with a diagnosis of liver cirrhosis in follow-up by the gastroenterology service of the Hospital de Especialidades del CMN la Raza in the year 2023.The prevalence of polypharmacy will be evaluated, taking as the definition established by the World Health Organization as the consumption of 5 or more drugs.Drug interactions will be recorded and evaluated using the Lexicomp-online formulary tool, classifying them as X (said drug should be avoided), D (consider modification of therapy), C (requires therapy monitoring), B (no action required) A (no known interaction).For qualitative variables, descriptive statistics will be used through measures of central tendency and measures of dispersion. To know the association between these variables, it will be evaluated using Pearson correlation and to know the level of association between variables, it will be evaluated with cross tables and Chi square. The analysis will be carried out through the SPSS25 program. Results: A total of 100 patients were recruited, of which 35% were men and 65% were women, the average age was 57 years, the most frequent etiological entity associated with liver cirrhosis was MASLD, representing 45%, followed by 18% by primary biliary cholangitis and in third place chronic HCV infection with 13%. Among the most frequent comorbidities is type 2 diabetes (48%), followed by systemic arterial hypertension (32%), and hypothyroidism (18%). The classification of liver dysfunction found a predominance of Child Pugh B with 49%. The diagnosis of polypharmacy (use of more than 5 drugs) had a prevalence of 44%. The analysis of probable pharmacological interactions found a percentage of D and C interaction of 18% and 60%, with no X or A interactions reported.Through Chi square analysis, no association was found between MASLD etiology and polypharmacy. By degree of liver dysfunction, an association was found between the Child Pugh C classification and polypharmacy with a P value of 0.002 and a relative risk of 6.25 (CI 1.73-25.27). The association between drug interactions D, and C were associated with polypharmacy with a statistically significant P with a RR of 9.1 and 9.7 respectively. Conclusions: The prevalence of polypharmacy in our population was higher than that reported in the international literature, placing patients with liver cirrhosis at high risk of adverse effects and drug interactions, with up to 60% reported in our population with classification D. This should prompt a thorough review of the drugs consumed as well as close monitoring.